2023
DOI: 10.3389/fimmu.2023.1145268
|View full text |Cite
|
Sign up to set email alerts
|

Galectins as pivotal components in oncogenesis and immune exclusion in human malignancies

Abstract: Galectins are galactoside-binding proteins, exerting numerous functions inside and outside the cell, particularly conferring adaptation to stress factors. For most of them, aberrant expression profiles have been reported in the context of cancer. Albeit not being oncogenic drivers, galectins can be harnessed to exacerbate the malignant phenotype. Their impact on disease establishment and progression is not limited to making cancer cells resistant to apoptosis, but is prominent in the context of the tumor micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 166 publications
1
5
0
Order By: Relevance
“…Concerning galectin-2, a recent study demonstrated that it plays a crucial role in TNBC by contributing to the formation of an immunosuppressive microenvironment, possibly following the release of its form extracellular by the tumor cell ( 39 ). These observations add to prior studies establishing galectins as prime targets for improving the efficacy of immunotherapy within the tumor microenvironment ( 40 42 ). Galectin-2 has also been found in the cytosol and nuclei of gastric cancer cells ( 43 ).…”
Section: Where Are Galectins In Cancer Cells?supporting
confidence: 57%
“…Concerning galectin-2, a recent study demonstrated that it plays a crucial role in TNBC by contributing to the formation of an immunosuppressive microenvironment, possibly following the release of its form extracellular by the tumor cell ( 39 ). These observations add to prior studies establishing galectins as prime targets for improving the efficacy of immunotherapy within the tumor microenvironment ( 40 42 ). Galectin-2 has also been found in the cytosol and nuclei of gastric cancer cells ( 43 ).…”
Section: Where Are Galectins In Cancer Cells?supporting
confidence: 57%
“…In pancreatic cancer, the crucial role of CD44/TGFβ receptors (TβRI and TβRII) signalling is well admitted not only in epithelial-to-mesenchymal transition but also in the earlier ADM step. This hypothesis is very likely with regard to the ability of other galectins to bridge different receptors to promote carcinogenesis ( 70 72 ). The hypothesis that LGALS9 mediates TGFβ and CD44 signalling in KRAS-driven carcinogenesis will need further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The interacting partners of galectin-9 have been identified and are mainly expressed on the cell surface of different immune cells, including NK cells, effector T cells, Tregs, monocytes, macrophages, and neutrophils ( Table 2 and Figure 3 ). Galectin-9 studies have revealed an immunoregulation [ 105 ] within the TME. These molecules are displayed as transmembrane proteins that transduce signals from the cell surface to intracellular effectors to control immune cell proliferation, survival, and cytokine secretion [ 106 ].…”
Section: Human Galectinsmentioning
confidence: 99%